Impact of different blood pressure targets on cerebral hemodynamics in septic shock: A prospective pilot study protocol-SEPSIS-BRAIN. - Pedro Cury; Rogério da Hora Passos; Fernanda Alves; Sérgio Brasil; Gustavo Frigieri; Fabio S Taccone; Ronney B Panerai; Juliana Caldas (PLoS ONE)
Introduction Septic shock, a life-threatening condition, can result in cerebral dysfunction and heightened mortality rates. In these patients, disturbances in cerebral hemodynamics, as reflected by impairment of myogenic cerebral autoregulation (CA), metabolic regulation, expressed by critical closing pressure (CrCP) and reductions in intracranial compliance (ICC), can adversely impact septic shock outcomes. The general recommendation is to maintain a target mean arterial pressure (MAP) of 65 mmHg but the effect of different MAP targets on cerebral hemodynamics in these patients is not clear and optimal targets might be dependent on the status of CA. This protocol aims to assess the cerebral hemodynamics profile at different pressure targets in septic shock patients. Methods Prospective, non-randomized, single-center trial, which will study cerebral hemodynamics in patients with septic shock within 48 hours of its onset. Patients will be studied at their baseline MAP and at three MAP targets (T1: 65, T2: 75, T3: 85 mmHg). Cerebral hemodynamics will be assessed by transcranial Doppler (TCD) and a skull micro-deformation sensor (B4C). Dynamic CA will be expressed by the autoregulation index (ARI), calculated by transfer function analysis, using fluctuations of MAP as input and corresponding oscillations in cerebral blood velocity (CBv). The instantaneous relationship between arterial blood pressure and CBv will be used to estimate CrCP and resistance-area product (RAP) for each cardiac cycle using the first harmonic method. The B4C will access ICC by intracranial pressure waveforms (P2/P1). The primary aim is to assess cerebral hemodynamics (ARI, CrCP, RAP, and P2/P1) at different targets of MAP in septic shock patients. Our secondary objective is to assess cerebral hemodynamics at 65mmHg (target recommended by guidelines). In addition, we will assess the correlation between markers of organ dysfunction (such as lactate levels, vasoactive drugs usage, SOFA score, and delirium) and CA. Ethics and dissemination The results of this study may help to understand the effect of the recommended MAP and variations in blood pressure in patients with septic shock and impaired CA and ICC. Furthermore, the results can assist large trials in establishing new hypotheses about neurological management in this group of patients. Approval was obtained from the local Ethics Committee (28134720.1.0000.0048). It is anticipated that the results of this study will be presented at national and international conferences and will be published in peer-reviewed journals in 2024 and 2025. Trial registration Trial registration number: NCT05833607. https://clinicaltrials.gov/study/NCT05833607.